PROHIBITION AS ONTOLOGICAL BASIS OF THE RUSSIAN LEGAL REALITY - A. V. Skorobogatov; N. N. Rybushkin (Russian Journal of Economics and Law)
Objective: to identify characteristics of the nature, content and functioning of prohibition in the legal reality of Russia.Methods: the methodological basis of research is the dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, as well as a postmodern paradigm, giving the opportunity to explore the legal reality at different levels. Dialectical approach and postmodern paradigm determined the choice of specific research methods: comparative, hermeneutic, discursive.Results: the paper proposes a definition of prohibition as a state- (socio-) volitional constraining (limiting) means that under the threat of legal liability is intended to prevent the wrongful act of the subject (physical or legal entity) and ensure the maintenance of law and order. Prohibition is a necessary means of ensuring the discipline of public relations, and the consolidation of legal values designed to assure the effectiveness of legal regulation. Scientific novelty: for the first time, the article shows that prohibition as a legal category is the ontological basis of legal reality and acts as a determining factor in the content and focus not only of law-making and law enforcement, but legal behavior as well.Practical significance: the main provisions and conclusions of the article can be used in research and teaching when considering questions about the nature, content and functioning of prohibitions.